The Early Acheulean technology of Barranc de la Boella (Catalonia, Spain). (30th January 2016) - Mosquera, M.; Ollé, A.; Saladié, P.; Cáceres, I.; Huguet, R.; Rosas, A.; Villalaín, J.; Carrancho, A.; Bourlès, D.; Braucher, R.; Pineda, A.; Vallverdú, J.
Abstract: Since 2007, excavations at Barranc de la Boella (Tarragona, Catalonia, Spain) have revealed three localities with rich archaeo-paleontological assemblages: La Mina, El Forn and Pit 1. Palaeontology, palaeomagnetism and cosmogenic analyses have dated these localities to close to 1 Ma. The presence of Mammuthus meridionalis, Hippopotamus antiquus, Stephanorhinus cf. hundsheimensis, Mimomys savini and Victoriamys chalinei stand out in the sample of macro and micro-mammals. The lithic assemblages from the three sites are made up of percussion cobbles, choppers, chopper-cores, cores, simple flakes, and some retouched flakes: mainly denticulates and notches. In the case of the El Forn and Pit 1 localities, two large cutting tools have been recovered: a cleaver-like tool and a pick made of hard-wearing schist. The lithic assemblage of Pit 1, which includes several refitting lithic sets, is closely associated with the remains of a young-adult Mammuthus meridionalis, in a clear butchering site context. This evidence suggests that Barranc de la Boella is the oldest European Early Acheulean site, and one of the oldest butchering site on the subcontinent during the late Early Pleistocene. The study of the variability among these three localities in similar environmental conditions, together with information from other sites, are discussed in order to gain further knowledge about the appearance of the Acheulean in Europe, and its continuity or discontinuity in relation to pre-existing technologies.